Strengthening Patient Engagement in Primary Care: A Systematic Review of Family Medicine Principles, Homecare Accessibility, and Doctor-Patient Relationship Quality - Kusuma, Luthfi Primadani; Praswati, Aflit Nuryulia; Romadhon, Yusuf Alam (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Patient engagement is a fundamental determinant of primary care effectiveness, particularly in semi-rural settings where structural barriers and relational discontinuities undermine access and outcomes. Family medicine principles-continuity, coordination, and comprehensiveness-and multidimensional accessibility (time, distance, cost) are frequently proposed interventions, yet their combined influence on patient engagement and the mediating role of doctor-patient relationship quality remain incompletely synthesized. To systematically synthesize empirical evidence on the effects of family medicine principles and homecare accessibility on patient engagement in primary care, and to evaluate how the quality of the doctor-patient relationship mediates these effectsMethodology: Systematic review following PRISMA guidelines, we searched Scopus, PubMed, and ScienceDirect for peer-reviewed studies published from 2013 to 2025 that addressed family medicine values, accessibility dimensions, homecare models, and interpersonal dynamics in primary care. Thirty-eight studies meeting predefined inclusion criteria underwent thematic synthesis and critical appraisal to identify recurrent mechanisms, contextual moderators, and measured engagement outcomes.Results: The synthesis identified three interrelated mechanisms through which primary care interventions influence engagement: (1) family medicine principles-especially continuity and care coordination-foster trust and longitudinal patient commitment; (2) accessibility along temporal, spatial, and financial axes predominantly affects utilization and perceived feasibility of care, with temporal barriers most recurrent in the evidence base; (3) doctor-patient relationship quality-characterized by effective communication, empathy, and cultural competence-consistently mediates the impact of structural and organizational factors on patient activation, adherence, and sustained engagement.Applications/Originality/Value: Integrating family medicine principles with targeted improvements in time, distance, and cost accessibility amplifies patient engagement when relational quality is actively cultivated. Implementation strategies should prioritize continuity of care and communication training alongside accessibility interventions to optimize patient-centered outcomes in semi-rural primary care settings.